2010
DOI: 10.1590/s0102-76382010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da ultrafiltração modificada na função pulmonar e necessidade de hemotransfusão em pacientes submetidos à revascularização do miocárdio

Abstract: Efeitos da ultrafiltração modificada na função pulmonar e necessidade de hemotransfusão em pacientes submetidos à revascularização do miocárdioThe effects of modified ultrafiltration on pulmonary function and transfusion requirements in patients undergoing coronary artery bypass graft surgery Abstract Objective: The inflammatory response after cardiac surgery increases vascular permeability leading to higher mortality and morbidity in the post operative time. The modified ultrafiltration (MUF) has shown benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…An additional 55 articles were excluded on the following basis: 1) no data on the primary outcome of interest, 2) transfusion outcome with incomparable units, 3) pediatric patient population, 4) intervention other than MUF or CUF, 5) meta-analysis or systematic review, 6) combined use of MUF and CUF in study group, and 7) lack of nonultrafiltration control group. Nine studies 3,5,10,[13][14][15][16][17][18][19] (n = 47,985 patients) were included in the final analysis. There were 7 RCTs (n = 928) 3,10,13-17 and 2 observational studies (n = 47,007) 5,18 included in the analysis.…”
Section: Literature Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 55 articles were excluded on the following basis: 1) no data on the primary outcome of interest, 2) transfusion outcome with incomparable units, 3) pediatric patient population, 4) intervention other than MUF or CUF, 5) meta-analysis or systematic review, 6) combined use of MUF and CUF in study group, and 7) lack of nonultrafiltration control group. Nine studies 3,5,10,[13][14][15][16][17][18][19] (n = 47,985 patients) were included in the final analysis. There were 7 RCTs (n = 928) 3,10,13-17 and 2 observational studies (n = 47,007) 5,18 included in the analysis.…”
Section: Literature Identificationmentioning
confidence: 99%
“…Of note, 6 included studies did not report mean weight or body surface area of study groups. 5,10,13,[15][16][17] Supplemental Figure 2 illustrates the Cochrane Risk of Bias 2.0 reporting for all included RCT studies. Two of 7 studies demonstrated an overall high risk of bias due to randomization process and deviations from intended interventions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of other knowledge came along with this new technology relating to the physiology of circulation, the body's reactions to surgical aggressions and the domain knowledge in relation to the internal environment, in which all our cells are immersed and where metabolism is developed with the production of energy that makes us live [16][17][18][19][20][21][22][23][24][25][26][27]. These studies resulted in the understanding of homeostasis, a complex system of self-regulation responsible to maintain the multiple vital parameters within normal levels, during production of the energy previously cited.…”
mentioning
confidence: 99%